SISTEM INFORMASI E-COMMERCE TOKO HIJAB BERBASIS WEB DENGAN METODE EXTREME PROGRAMMING - Nurlistiani, Rini; Kurniawan, Hendra; Yuliawati, Dona; Maria, Okta (LP2M Institut Informatika Dan Bisnis Darmajaya, 2024)
Development of increasingly modern technological devices can provide advantages for entrepreneurs to market services and products with the aim of expanding market share with a wide reach. The scope of product sales in an area becomes ineffective in being able to compete to attract consumer interest. The role of information technology can be carried out using internet media so that consumers can access it online or can be called e-commerce. The object of this research was carried out at a hijab shop in the Natar area, South Lampung. The problems that exist include the sales process which is carried out directly, such as consumers coming to the shop to buy products, which has an impact on operational costs, energy and time, especially consumers who are in areas where they cannot see information on the availability of the product they want to buy. The system development method used is Extreme Programming. The results obtained are that the use of the website is running well, as evidenced by the results of system testing using blackbox testing of 91.66%, which means that this e-commerce information system is running successfully and can be used by consumers, especially in the South Lampung area and its surroundings.